The role of a university professor in developing core values and promoting positive behavior of applied accounting students at King Khalid University and its obstacles from the professors’ point of view - Yagoub, Mona Abdelrhman (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the role of the university professor in developing core values and promoting the positive behavior of applied accounting students at King Khalid University and its obstacles from the professors’ point of view.) a faculty member, and the results of the study concluded that the university professor has a significant and important role in developing and enhancing the core values and positive behavior of the students of the applied accounting program; Through the development of curricula and courses with an average of (4.65 out of 5) and the application of effective teaching methods and strategies with an average of (4.55), both of which have a (very high) role rating, while there are obstacles that limit the practice of teachers for this role; with an average of (4.13) and a (large) level. The results of the study also confirmed the presence of statistically significant differences at the level (α≤0.05); Between the points of view of the study sample in the axes of the study according to the variables (academic qualification, scientific specialization, years of experience).Based on the results, the researcher recommended the necessity of clearly defining the role of the university professor in developing curricula and courses to develop and enhance the core values and positive behavior of students.